Evaluating the use of building information modelling in resort development in republic of the Maldives - Tholhath, Ahmed (2013)
Ineffective collaboration within project participants during building process is causing poor implementation coordination for sustainable development of resort projects in Maldives. Concept design, detail design, construction and the facility management are separate stages of project awarded to different firms for their implementation. These need to be collaborated during project lifecycle. Attainment of quality and productivity in the construction industry has long been a problem in Maldives. A case study consisting of two similar resort projects with the same bed capacity and star rating within the Ari atoll (Maldives) was undertaken for the purpose of study. The problems of managing concerns of implementation coordination and technological integration in developing sustainable resort projects in the Maldives were evaluated. Utilization of Building Information Modelling (BIM) for implementation coordination during building process in Maldives and the implications on two selected projects were evaluated. The study have identified eleven conditions—planning errors, design errors, amendments due to design errors, misinterpretation of drawings,use of 3D models, discontinuation of information, construction practicality, onsite errors, use of prefabrication, amendments due to construction errors and time extensions for construction—from both case projects that are related to their increasing of quality and productivity while decreasing cost and duration phenomenon. The study found careful contractual and procurement method must could accomplish project objectives. The study recommends BIM for improving implementation coordination which could increase construction productivity and prefabrication with less rework on site. Better coordination to minimize errors in design, construction and management of the projects with BIM accounts for the improvement to the project lifecycle of the project to build a sustainable and eco-friendly construction industry. Sustainable development can significantly reduce adverse human impacts on the natural environment while simultaneously improving quality of life and economic well-being. Therefore the construction industry needs to integrate BIM for the successful implementation of construction projects towards sustainable development. Effective collaboration will improve implementation coordination and integration through BIM during building process with innovative planning in the Maldives, hence improve construction industry and develop sustainable resort projects. Achieving sustainability through coordination and integration by BIM and identifying relationship between ecological and socio-economic systems will be the main contribution to the construction industry in Maldives.